PELAKSANAAN ISBAD NIKAH DAN DISPENSASI NIKAH DI KOTA PADANG - Agustini, Sri (Ensiklopedia Sosial Review, 2021)
Marriage is a marriage bond (contract) carried out in accordance with the provisions of Islamic law and teachings. Meanwhile, marriage is a marriage ceremony that is identified with the consent and kabul process. Literally, marriage is a sacred bond and is carried out by a combination of religious and state regulations. In order for the marriage bond to have legal certainty administratively, the marriage has been regulated in law. With the enactment of these rules, marriages that are not in accordance with the law cause their own problems in society. Especially about unregistered marriages and early marriage or marriages by minors.